Implementation Of Restorative Justice Approach In The Settlement Of Narcotics Crime Cases : Research Study At Bintan Police Station - Suardi Suardi; Ramlan Ramlan; Erniyanti Erniyanti; M. Soerya Respationo; Nicha Suwalla (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
The phenomenon of narcotics abuse is a serious problem that requires special handling, especially in Indonesia. Traditional approaches that emphasize criminal punishment have not proven to be fully effective in resolving this problem. This study examines the implementation of the restorative justice approach in resolving narcotics crime cases at the Bintan Police. The restorative justice approach emphasizes victim rehabilitation, perpetrator rehabilitation, and reconciliation between perpetrators and victims as an alternative to prison sentences. The purpose of this study is to analyze the legal arrangements that support the restorative justice approach in narcotics cases, evaluate the implementation of this approach in the Bintan Police, as well as identify the obstacles faced and formulate relevant solutions. The research method used is a qualitative method with a case study approach, involving in-depth interviews with police officers, medical personnel, and other related parties, as well as analysis of applicable legal documents and policies. The results of the study show that although there are efforts to implement a restorative justice approach in the Bintan Police, the implementation is not optimal. The main obstacles faced include a lack of adequate rehabilitation facilities, limited understanding among law enforcement officials, and social stigma against narcotics addicts. The study found that better coordination between institutions, intensive training and socialization, and improved rehabilitation facilities are needed to overcome these barriers. Based on these findings, the suggestions given include increasing the capacity and quality of rehabilitation facilities by the government, further training for police officers on restorative justice approaches, and educational campaigns for the community to reduce stigma against narcotics addicts. With these steps, it is hoped that the restorative justice approach can be applied more effectively, providing a more humane and recovery-oriented solution in handling narcotics cases at the Bintan Police.